2016
DOI: 10.5380/rmu.v3i1.46380
|View full text |Cite
|
Sign up to set email alerts
|

O Impacto Do Diabetes Mellitus Tipo 2 Na Qualidade De Vida

Abstract: Background: Diabetes Mellitus (DM) is a chronic disease of great importance, both for the impact it causes on the health, as the disorders, complications and losses that may originate in quality of life. Objective: Evaluate the impact of type 2 diabetes on quality of life of patients registered in basic health units in Curitiba -PR. Method: Cross-sectional observational study. Sample of 983 patients older than 18 years of both sexes, DM2 patients for over a year, randomly selected and registered in Basic Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
2
0
6
Order By: Relevance
“…A study carried out in Brazil that measured the quality of life of patients, identified that among the subjects studied, physical and emotional factors were the most determinant for their quality of life, and the emotional impact occupied the second place, corresponding to a value of 77.2%. The authors explained that diabetes mellitus interferes in the patients’ quality of life in a negative way [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study carried out in Brazil that measured the quality of life of patients, identified that among the subjects studied, physical and emotional factors were the most determinant for their quality of life, and the emotional impact occupied the second place, corresponding to a value of 77.2%. The authors explained that diabetes mellitus interferes in the patients’ quality of life in a negative way [19]. …”
Section: Discussionmentioning
confidence: 99%
“…We identified in the speeches of the participants that food is one of the most difficult factors to control the illness. Other studies [19, 29] have stated that the negative impact on the quality of life is influenced by the new lifestyle, which should be adopted, and especially because people with diabetes need more food restriction, which has a greater impact on therapeutic participation and health care. Thus, food re-education is one of the greatest challenges faced by some people with diabetes mellitus, where negative feelings related to food control occur, such as the difficulty to meet the goals set by the health team and consequent frustration [18].…”
Section: Discussionmentioning
confidence: 99%
“…e "Quantas vezes você come algo que não deveria?". Estudo de Diaz et al 23 mostra semelhança do impacto na qualidade de vida nestes aspectos, já que a maioria dos participantes também se sentiu frequentemente incomodada por ter diabetes, além de cerca de 90% dos entrevistados se sentirem restritos pela nova dieta, além de afirmarem não Quanto à relação entre as médias dos domínios do questionário DQOL e o uso de insulinas, destaca-se que, mesmo não havendo uma diferença estatística significativa, acredita-se que há uma diferença em relação à qualidade de vida dos entrevistados. O domínio preocupações do DQOL apresentou o pior escore na comparação insulinas convencionais versus análogas.…”
Section: Discussionunclassified
“…Autores apontam a capacidade do DM em causar várias alterações na saúde dos pacientes, afetando sua vida cotidiana, principalmente aqueles que usam insulina e têm mais de 10 anos de doença, o que reforça para a necessidade de orientações quanto a doença, prevenção das complicações e autocuidado 31 . O incentivo às práticas saudáveis, controlando os fatores de risco associados ao diabetes, pode diminuir a incidência da doença e suas complicações, demonstrando o importante papel da enfermagem na educação em saúde e na implementação de medidas preventivas.…”
Section: Discussionunclassified